Sequential explanatory technological pedagogical and content knowledge of madrasah teachers in Jambi - Sanjaya, Budi; Syefrinando, Boby; Hidayat, Wahyu (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2024)
This study aims to describe the structural model of Sequential Explanatory Technological Pedagogical and Content Knowledge (TPACK) of Madrasah Teachers in Jambi Province.This research involved 132 teachers for surveys and 5 teachers for interviews. Descriptive statistics, t-test, Anova, and SEM-PLS were used in quantitative data analysis, while qualitative data was carried out using descriptive thematics. The findings show that Madrasah teachers' TPACK is at a good category level. There are no differences in teachers' TPACK levels based on gender, certification status, madrasa level, age, teaching experience, and field of study. Technological pedagogical knowledge (TPK) has a stronger influence on technological pedagogical and content knowledge (TPACK) compared to technological content knowledge (TCK) and pedagogical content knowledge (PCK). Teachers need support from schools and communities to increase TPACK knowledge in addition to from self-awareness to developing competence as well as several other information that have been discussed in the discussion of this research. Teachers should increase their TPACK knowledge so that they can confidently implement technology in their learning.